Polinización del chayote Sechium edule (Jacq.) Swartz en Costa Rica - Wille, Alvaro; Orozco, Enrique; Raabe, Carlos (Revista de Biología Tropical, 1983)
Pollinating insects of Sechium edule (Cucurbitaceae) were classified into primary and secondary according to their abundance and effectiveness as pollen collectors. Among the total of 55 insect species found in Costa Rica pollinating the plant, 28 were identified as primary meliponid bees of the genus Trigona (Apidae), the rest were secondary pollinators: 15 species of wasps (Vespidae); 5 species of bees of the family Halictidae, 3 species of Anthophori da e and 4 species of Apidae. The plants were distributed altitudinally from almost 0 to 2000 m. As altitude increases, primary pollinators diminish; almost all were collected under 500 m; 30% of the secondary pollinators (the highest counts) were obtained over 1500 m. The higher, frequencies of pollinators (44.8 average) were observed between 500 and 999 m. The lower frequencies correspond to the low lands. Only four pollinators were really abundant: Trigona (Trigona) corvina, T. (Partamona) cupira, T. (Trigona) fulviventris and T. (Trigona) fuscipennis. The first two are the most efficient. These two species are abundant between 500 and 1000 m, where the best producing plants are found. Trigona fuscipennis belongs in the low lands and is the major pollinator there. Trigona fulviventris is less frequent between 500 and 1499 m and exhibits high frequencies in low and high altitudes. This peculiar distribution could be due · to the fact that this specie s is not aggressive and therefore less able to compete with Trigona corvina and T. cupira.